More On Stimulant Drugs In Sports - Abd Razak, Dzulkifli (1996)
APART FROM AMPHETAMINES AND other realtes substances, there are many other drugs that are used in sports that could produce similar effects. Although they are classed differently in medical usage, they are nevertheless doping agents and thus banned in international sporting events. Below are some of the more common substances being misused. Ephedrine Just a few hours before the opening ceremony of the 26th Olympics, there was a report about a Norwegain canoeist who failed a drug test for ephedrine, another type of stimulant, at a competition in the German City of Duisburg in June. Consequently, he was dropped from the fourman kayak team and banned from competing in Atlanta. The canoeist, Peter Ribe was a bronze medalist at the 1993 world championships in the double kayak (K2). He claimed that he had taken a herbal product that was a subsequently found to contain the substance